How do breastfeeding workplace interventions work?: a realist review - Kathrin Litwan; Victoria Tran; Kate Nyhan; Rafael Pérez-Escamilla (BMC, 2021)
Abstract Background Women are representing an increasing share of the labor force, thus, raising the need to accommodate breastfeeding working mothers at the workplace. While there is an emerging body of evidence supporting the positive influence of workplace lactation programs on breastfeeding outcomes, there is a lack of literature on the mechanisms underlying those interventions. Aims of this realist review were three-fold: to uncover underlying mechanisms, determine who benefits the most from such interventions and important contextual factors influencing uptake. Methods Purposive bibliographic searches on Medline, Web of Science Core Collection, CINAHL, Global Health, LILACS, Global Index Medicus, Business Source Complete, Proquest Dissertations and Theses and Open Access Theses and Dissertations were conducted to identify relevant publications. Included publications (qualitative and quantitative) described interventions aiming to improve the breastfeeding behavior of working mothers, that were initiated by the employer, reported on breastfeeding outcomes and had a clearly defined workplace. Publications only focusing on maternity leave or that were not published in English, Spanish, Portuguese or German were excluded. A realist approach was followed to identify how workplace interventions work, who benefits the most and the important contextual factors. Results The bibliographic search yielded a total of 4985 possible publications of which 37 publications were included in the realist analysis. Effective workplace breastfeeding interventions activate three mechanisms: 1) awareness of the intervention, 2) changes in workplace culture, manager/supervisor support, co-worker support and physical environments, and 3) provision of time. Contextual factors such as the distance between the workplace and the infant and the type of workplace may influence the degree of activation of the underlying mechanisms for programs to positively impact breastfeeding outcomes. Conclusions In order to be effective, workplace breastfeeding interventions need to: raise awareness of the intervention(s) available among working mothers as well as their work environment, change the workplace culture, foster manager/supervisor support and co-workers support, provide enough time and adequate space and facilities for women to breastfeed or express breastmilk during the workday.